(untitled) (Contemporary Mathematics, 2024)
This scientific research investigates the fractional-order compartmental model of cervical cancer. The human papillomavirus (HPV) is responsible for the development of cervical cancer. The Caputo-Fabrizio fractional operator, which includes a section for treatment with antiretroviral drugs, is employed to examine this worldwide phenomenon. The mathematical model of cervical cancer that has been proposed recently is an extension of the integer-order model. The fractional derivative technique is a novel approach for these types of biological models. This paper employs fixed point theory to provide requirements for the existence, uniqueness, and stability of the fractional order cervical cancer model, utilizing the Caputo- Fabrizio operator. We have initially found an approximation solution to a proposed model via the iterative Laplace transform method, which is easily accessible. This approach integrates the Laplace transform technique with a reliable, novel iterative method. We evaluated parameters indicating the advancement of the illness and presented the numeric simulations. The observed outcomes indicate that a fractional factor has a crucial effect on controlling cervical cancer.